Effectiveness of green betel leaf and lime extract against Staphylococcus aureus and Escherichia coli - R.Y Gloria; RAHMA YULIYANI; MIA MAR'ATUSH SHOLIHA ASROR (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Gloria RY, Yuliyani R, Asror MMS. 2021. Effectiveness of green betel leaf and lime extract against Staphylococcus aureus and Escherichia coli. Biodiversitas 22: 3452-3457. Indonesian society utilizes biodiversity as source of medicinal herbs. Betel leaf and lime are included in traditional Indonesian medicinal plants that have antibacterial and antioxidant properties. One of the benefits of herbal medicinal plants of betel leaf and lime is that it can be used as a natural hand sanitizer. The purpose of this study was to test the effectiveness of naturally made hand sanitizer against Staphylococcus aureus and Escherichia coli by the combination of green betel leaf extract and lime extract. The experiment was performed by the Kirby-Bauer disc diffusion method. Results showed that a combination of 50% betel leaf extract and 50% lime extract inhibited the growth of S. aureus whereas, 75% betel leaf extract and 100% lime extract exhibited strong inhibition than 70% alcohol.